KOMPOSISI JENIS TUMBUHAN HERBA DI AREAL KAMPUS UNIVERSITAS TADULAKO PALU - Deddy Anaputra; Miswan Miswan; Ramadhanil Ramadhanil (Biocelebes, 2015)
The research titled ”Species Composition af Herb in the Area of Tadulako University Palu” was conducted from March to April 2015. The aim was to know the species composition of Herb in the area studied. The research was used survey method by using double plots. Herbs species were sampled in thirty (30) sublots of 2 x 2 m in size. All herbs collected for Herbarium specimen followed Pitopang et al (2011). Identification of vouchers and additional herbarium was done in the field as well as at UPT Natural Bioresources of Sulawesi and Laboratory of Biodiversity, The Department of Biology Fac. Sciences Tadulako University Palu. The result showed that were 62 herb species with 1.208 individual number, 22 familes. The dominant herb was Euphorbia hirta (IVI 14,68 %) where as the lowest was Portulaca grandiflora and followed by Achyranthes bidentata, Cereus hexagonus, Desmodium adscendens. Diversity index types in this study pertanied high, wich amounted to 3,73.Keywords : Tadulako University, Herb, INP, Species composition.